Evolving controls on mineralization in Patagonian microbial mats as inferred by water chemistry, microscopy and DNA signatures (Latin American Journal of Sedimentology and Basin Analysis, 2022)
In recent years resulting investigations in living microbialites have provided significant data that have been critical to disentangle the role of the various biotic and abiotic processes contributing to their development. Despite these efforts separating the impact and magnitude of these processes remain a difficult task. At present the Maquinchao Basin in northeastern Patagonia, Argentina, contains both fossil and living microbialites. Thus, the region provides a unique opportunity to investigate the impact of intrinsic and extrinsic parameters in carbonate precipitation. Early investigations (Austral summer 2011) in living microbialites concluded that organomineralization was related to both photosynthetic activity in the more surficial layer (green), and sulfate-reduction in the lower part (beige). Field investigations in the same area four years later showed that the pounds previously containing abundant active mats had dried out, and in general revealed the absence of globular structured clusters of minerals in the microbial mats. Here we present microscale investigations using optical microscopy and SEM along with the 16SrRNA gene sequence diversity, and the physico-chemical parameters of the hosting waters. They were carried out in successive seasonal samplings in November 2015, April-May 2016, August 2016, February 2017, and March 2018. All microbialite samples show regular occurrences of sulfate reducing bacteria (SRB) along with filaments of unknown origin. Carbonates are observed associated with erect filaments in shallow and active running water locations whereas the mineral phase is located below organic matter film in comparatively deeper and calmer water areas. Additionally, seasonal changes in the physico-chemical properties of the hosting waters indicate that extrinsic parameters, especially evaporation, might play a more substantial role in the precipitation of these carbonates than previously proposed. The environmental differences between 2011 and 2015 in meteorological conditions, regional volcanic activity and associated deposits in the basin are analyzed. We concluded that they are likely responsible of the decrease of the mineralization processes, and particularly those associated with photosynthetic activity.  These results call for caution when interpreting the degree of biological impact on the formation of microbialites in the geological record. Local extrinsic factors might have a changeable impact over time switching mineral precipitation from biotic to abiotic and vice-versa, which can be undistinguishable in fossilized microbialites.